2018
DOI: 10.3389/fpls.2018.00051
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen (N) Application Gradually Enhances Boll Development and Decreases Boll Shell Insecticidal Protein Content in N-Deficient Cotton

Abstract: Expression of insecticidal protein in transgenic Bacillus thuringiensis (Bt) is lower in cotton reproduction organs, especially during boll development period. The current study investigated the effects of nitrogen fertilization under nitrogen deficit on boll development and Bt toxin content in boll shell, which is the first target of boll worm harm. The protein synthesis and degradation in this process was also studied to uncover the underlying mechanism. Five nitrogen levels (under nitrogen deficiency) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Environmental conditions significantly affect the expression of exogenous proteins in Bt transgenic crops (Burke and Rieseberg, 2003; Chen et al, 2018b). Our results indicated that the expression of exogenous Cry1Ab/c protein in transgenic HH1 varied temporally and spatially in rice grown on saline-alkaline and farmland soils.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental conditions significantly affect the expression of exogenous proteins in Bt transgenic crops (Burke and Rieseberg, 2003; Chen et al, 2018b). Our results indicated that the expression of exogenous Cry1Ab/c protein in transgenic HH1 varied temporally and spatially in rice grown on saline-alkaline and farmland soils.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2019) reported that the fertilizer application rates influenced the Bt toxin expression, and the efficacy of Bt cotton reduced markedly if nitrogen rates were low during cotton growth. The recovery was further proved that nitrogen fertilizer enhanced Bt protein expression and insect resistance (Oosterhuis and Brown 2004;Wang et al 2012;Chen et al 2018). N deficit resulted in reduced Bt protein concentration (Chen et al 2004;Zhang et al 2017).…”
Section: Agronomic Practices On Insecticidal Efficacy In Bt Cottonmentioning
confidence: 93%
“…The concentration of Bt protein was significantly higher in leaves than that in other vegetative organs during the seedling period, including roots, stems and petioles, and ovaries expressed significantly more Bt toxin than pistils and stamens at the anthesis. The highest Cry1Ac expression was noted in leaves, followed by squares, bolls and flowers (Kranthi et al 2005;Chen et al 2017bChen et al , 2018. The ovary of flowers and rinds of green bolls, the most favored parts that bollworm attacked, exhibited the lowest toxin expression (Kranthi et al 2005).…”
Section: Insecticidal Efficacy Varied With Growth Period and Differenmentioning
confidence: 99%
See 2 more Smart Citations